An Error Analysis of Speaking Present Tense on English Conversation Program of PRO 2 Radio Bandar Lampung - Maryana Pandawa (Bandar Lampung University, 2015)
Making errors is expected to lead to some improvements in future learning. The general purpose of this research is to find out the announcers' errors in using simple present tense in speaking. This study uses descriptive qualitative research. The data were retrieved from announcers’ recording from English Conversation program of PRO 2 radio Bandar Lampung. Data analysis discovered that the announcers still made all of the four error types under the heading of surface strategy taxonomy. The error types that were identified in the announcers’ simple present tense sentence were ranked for the surface strategy taxonomy, errors in misformation amount to misformation, 70 errors (57,83%), followed by omission with 33 errors (27,27%) addition with 13 errors (10,71%) and misordering with only 5 errors (4,19%). These figures suggest that announcers should take more time to understand grammar further. Even though it was oral, but the announcers must use correct grammar to avoid miscommunication while transferring the message.